1999
DOI: 10.1093/rheumatology/38.11.1088
|View full text |Cite
|
Sign up to set email alerts
|

Apocynin, a plant-derived, cartilage-saving drug, might be useful in the treatment of rheumatoid arthritis

Abstract: Apocynin in vitro inhibits inflammation-mediated cartilage destruction without having adverse effects on cartilage. The latter may be an advantage of apocynin over many other non-steroidal anti-inflammatory drugs. Therefore, apocynin might have an added beneficial effect in protecting RA patients from joint destruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(47 citation statements)
references
References 27 publications
0
46
0
1
Order By: Relevance
“…This botanical compound is derived from the root of Picrorhiza kurroa (Dodd-O and Pearse, 2000) and has been used as a Chinese medicinal herb for treatment of a number of infectious and inflammatory diseases (Hougee et al, 2006;Kim-Mitsuyama et al, 2005;Lafeber et al, 1999). Studies from our laboratory showed the ability for apocynin to protect against delayed neuronal death induced by global cerebral ischemia in the gerbil .…”
Section: Discussionmentioning
confidence: 98%
“…This botanical compound is derived from the root of Picrorhiza kurroa (Dodd-O and Pearse, 2000) and has been used as a Chinese medicinal herb for treatment of a number of infectious and inflammatory diseases (Hougee et al, 2006;Kim-Mitsuyama et al, 2005;Lafeber et al, 1999). Studies from our laboratory showed the ability for apocynin to protect against delayed neuronal death induced by global cerebral ischemia in the gerbil .…”
Section: Discussionmentioning
confidence: 98%
“…Although therapeutic strategies focusing on the elimination of superoxide have been developed in animal models and in clinical cases, the effects of such reagents are still unclear [11,[30][31][32]. Therefore, in this study, we investigated whether inhalation of apocynin may influence hydrogen peroxide, nitrite and nitrate concentrations in airways in healthy subjects.…”
mentioning
confidence: 99%
“…Additionally, no changes in blood differential counts have been noticed. This may suggest that nebulized apocynin does not diffuse into the blood, and acts locally [32,57].…”
mentioning
confidence: 99%
“…Several microorganisms are able to convert ferulic acid to a wide range of aromatic compounds (Figure1). These include the following species: Aspergillus, Bacillus, Candida, Corynespora, Fusarium, Pseudomonas and many more (Dodd-o and Pearse, 2000;Engels et al, 1992;Lafeber et al, 1999;Pearse and Dodd-o, 1999;Peters et al, 2001;van den Worm et al, 2001;Walton et al, 2000). The major pathways of metabolism can be summarized as: i) Nonoxidative decarboxylation to give 4-vinylguaiacol (4-hydroxy-3-methoxystyrene) (Rosazza et al, 1995;Lee et al, 1998;Donaghy et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the pharmaceutical use of steroidal drugs is becoming increasingly controversial, owing to multiple side-effects, creating a need for new and safe alternative antiinflammatory agents (Lafeber et al, 1999;van den Worm et al, 2001).…”
Section: Introductionmentioning
confidence: 99%